Intuitive virtual reality based frontal-midline theta neurofeedback: a feasibility study in young ages - Gerber, Stephan M.; Riddle, Justin; Lagarde, Hadden; Zhang, Mengsen; Frohlich, Flavio (Frontiers in Virtual Reality, 2025)
BackgroundNeurofeedback is a method to modulate neural activity, such as frontal-midline theta oscillations. Given the emerging role of pathologically disrupted neuronal oscillations in psychiatric disorders, neurofeedback has potential as a novel therapeutic intervention. Participant immersion in the neurofeedback paradigm is critical to its efficacy. Here, we tested whether virtual reality enabled immersion and rapid acquisition of the ability to intentionally modulate frontal-midline theta oscillations.MethodsWe developed a neurofeedback task in which participants were instructed to clean up trash in a virtual underwater environment with their own thoughts. Unbeknownst to the participant, the amount of trash was updated as a function of frontal-midline theta power estimated from real-time electroencephalography recording. The neurofeedback blocks were interleaved with a working memory task, which is known to increase frontal-midline theta oscillations.ResultsThe study involved 29 participants (Mean age = 24.62 years, SD = 9.31). By the end of the first block, 70% of participants successfully increased and sustained their frontal-midline theta oscillations. The amplitude of frontal-midline theta during neurofeedback was greater than rest but not as strong as during the working memory task.ConclusionWe suggest that virtual-reality-based neurofeedback is highly immersive, causes minimal discomfort and increases theta oscillations with a brief learning period. Neurofeedback is a feasible method of increasing neural activity similar to working memory tasks and a promising method for training individuals to increase endogenous theta oscillations. Future research should investigate potential transfer effects into cognitive domains to increase cognitive control and top-down control.